Strategic appraisal : United States air and space power in the 21st century - Khalilzad, Zalmay; Shapiro, Jeremy; Ochmanek, David A.; Byman, Daniel, 1967-; Waxman, Matthew C., 1972-; Stevens, Donald, 1958-; Gibson, John, 1935-; Preston, Bob, 1951-; Baker, John C., 1949-; Nichiporuk, Brian, 1966-; Buchan, Glenn C.; Mesic, Richard, 1943-; et al. (Santa Monica, CA : RAND, 2002)
Change--in international relations, in technology, and in society as a whole--has become the idiom of our age. One example of these changes has been an increasing recognition of the value of air and space assets for handling nearly every contingency from disaster relief to war and, consequently, increasing demand for such assets. These developments have created both challenges and opportunities for the U.S. Air Force. This, the fourth volume in the Strategic Appraisal series, draws on the expertise of researchers from across RAND to explore both the challenges and opportunities that the U.S. Air Force faces as it strives to support the nation's interests in a challenging technological and security environment. Contributors examine the changing roles of air and space forces in U.S. national security strategy, the implications of new systems and technologies for military operations, and the role of nuclear weapons in U.S. security strategy. Contributors also discuss the status of major modernization efforts within the Air Force, and the "bill of health" of the Air Force, as measured by its readiness to undertake its missions both today and in the future.
Introduction: The Price of Success / Jeremy Shapiro -- Forces for What? Geopolitical Context and Air Force Capabilities / Zalmay Khalilzad, David Ochmanek, and Jeremy Shapiro -- The Future of U.S. Coercive Airpower / Daniel L. Byman, Matthew C. Waxman, and Jeremy Shapiro -- Modernizing the Combat Forces: Near-Term Options / Donald Stevens, John Gibson, and David Ochmanek -- Space Challenges / Bob Preston and John Baker -- U.S. Military Opportunities: Information-Warfare Concepts of Operation / Brian Nichiporuk -- Nuclear Weapons and U.S. National Security Strategy for a New Century / Glenn Buchan -- Countering Weapons of Mass Destruction and Ballistic Missiles / Richard F. Mesic -- Providing Adequate Access for Expeditionary Aerospace Forces / David Shlapak -- A Vision for an Evolving Agile Combat Support System / Robert Tripp, C. Robert Roll, Jr., Lionel Galway, Timothy Ramey, John Drew, Mayhar Amouzegar, and Clifford Grammich -- Strategic Sourcing in the Air Force / Frank Camm -- Ready for War but Not for Peace: The Apparent Paradox of Military Preparedness / Carl Dahlman and David Thaler .
"Project Air Force."
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Keywords: United States. -- Air Force -- Planning; Air power -- United States; Astronautics, Military -- United States; World politics -- 21st century; Electronic books